Maternal transfer of dioxin-like compounds in artificially matured European eels. (August 2017) - Freese, Marko; Sühring, Roxana; Marohn, Lasse; Pohlmann, Jan-Dag; Wolschke, Hendrik; Byer, Jonathan D.; Alaee, Mehran; Ebinghaus, Ralf; Hanel, Reinhold
Abstract: Several eel species of the genus Anguilla are considered endangered due to a severe decline in recruitment. Up to now, the reasons for this threatening development are not fully understood. The eel's highly specialized biology can lead to explicitly high accumulation of globally distributed organic lipophilic contaminants during its continental life. Because of this and due the particular toxicological sensitivity of early life stages of oviparous organisms towards dioxin-like compounds, it is crucial to improve our understanding concerning toxicokinetics and maternal transfer of organic contaminants in eels. This study presents analytical data on maternal transfer of dioxin-like (dl) compounds in relevant tissue samples taken from artificially matured and non-matured European silver eels ( Anguilla anguilla ) from German inland waters using gas chromatography coupled with mass spectrometry (GC/MS) and high-resolution mass spectrometry (GC/HRMS). Detected concentrations revealed a lipid-driven transfer of targeted compounds from muscle-fat-reserves to gonads and eggs respectively, with no distinct preferences concerning the chlorination degree of targeted compounds. Dl-PCBs were shown to contribute the major share of toxicity equivalents found in analysed eel tissues. Maternal muscle tissue to egg concentration ratios in wet weight–based samples had a mean of 6.95 ± 1.49 in accordance with the differences in total lipid content in the respective body matrices. Dioxins and furans in analysed samples were (from a toxicological point of view) of less relevance. Furthermore it was shown that muscle concentrations in silver eels could be used in future assessments to make conservative predictions for expected egg concentrations in female eels. Graphical abstract: Highlights: Analytical evidence and quantification of maternally transferred dioxin like compounds in European eel eggs. Transfer of DLCs follows lipid concentration in respective body compartments. Results can help identify suitable habitats for stocking measures.